Radicalism Among Students: A Study of Perception of Radicalism of Indonesian and Malaysian Students - Idzam Fautanu (UIN Sunan Gunung Djati, 2022)
This article examines radicalism as a socio-religious phenomenon in constructing ideological and political struggles. This study aims to determine the perceptions of Indonesian-Malaysian students regarding radicalism based on religious understanding obtained at the university. This research uses qualitative methods through online interview data collection, focus group discussions (FGD), and a descriptive-interpretative analysis literature study. This study found several findings, namely: students' perceptions of the level of radicalism were divided into three levels: 1) high (extremism, socio-political movement for political purposes); 2) medium (intolerance); 3) low (exclusive, does not accept differences of opinion). However, it should be noted that the perception of Indonesian students is more diverse regarding the level of radicalism, in contrast to the perception of Malaysian students who view the level of radicalism as narrower. This is due to the political influence of each country. Furthermore, the power of religious understanding at universities regarding the level of radicalism on Indonesian and Malaysian students is different due to the reception of information in class, discussions in communities/organizations, and information from social media. This article contributes to increasing the discussion on youth's response to religious-based radicalism so that various parties, including the government and academics, can carry out a more comprehensive anti-radicalism campaign.